Comparison of the Gene Coding Contents and Other Unusual Features of the GC-Rich and AT-Rich Branch Probosciviruses - Paul D. Ling; Simon Y. Long; Jian-Chao Zong; Sarah Y. Heaggans; Xiang Qin; Gary S. Hayward (mSphere, 2016)
ABSTRACT Nearly 100 cases of lethal acute hemorrhagic disease in young Asian elephants have been reported worldwide. All tested cases contained high levels of elephant endotheliotropic herpesvirus (EEHV) DNA in pathological blood or tissue samples. Seven known major types of EEHVs have been partially characterized and shown to all belong to the novel Proboscivirus genus. However, the recently determined 206-kb EEHV4 genome proved to represent the prototype of a GC-rich branch virus that is very distinct from the previously published 180-kb EEHV1A, EEHV1B, and EEHV5A genomes, which all fall within an alternative AT-rich branch. Although EEHV4 retains the large family of 7xTM and vGPCR-like genes, six are unique to either just one or the other branch. While both branches display a highly enriched distribution of A and T tracts in intergenic domains, they are generally much larger within the GC-rich branch. Both branches retain the vGCNT1 acetylglucosamine transferase and at least one vOX-2 gene, but the two branches differ by 25 genes overall, with the AT-rich branch encoding a fucosyl transferase (vFUT9) plus two or three more vOX2 proteins and an immunoglobulin-like gene family that are all absent from the GC-rich branch. Several envelope glycoproteins retain only 15 to 20% protein identity or less across the two branches. Finally, the two plausible predicted transcriptional regulatory proteins display no homology at all to those in the alpha-, beta-, or gammaherpesvirus subfamilies. These results reinforce our previous proposal that the probosciviruses should be designated a new subfamily of mammalian herpesviruses. IMPORTANCE Multiple species of herpesviruses from three different lineages of the Proboscivirus genus (EEHV1/6, EEHV2/5, and EEHV3/4/7) infect either Asian or African elephants, but the highly lethal hemorrhagic disease is largely confined to Asian elephant calves and is predominantly associated with EEHV1. In the accompanying paper [P. D. Ling et al., mSphere 1(3):e00081-15, 10.1128/mSphere.00081-15 ], we report the complete 206-kb genome of EEHV4, the third different species causing disease in Asian elephants and the first example of a GC-rich branch proboscivirus. To gain insights into the nature and differential properties of these two very anciently diverged lineages of elephant herpesviruses, we describe here several additional unusual features found in the complete GC-rich genome of EEHV4 with particular emphasis on patterns of divergence as well as common unique features that are distinct from those of all other herpesviruses, such as the enlarged AT-rich intergenic domains and gene families, including the large number of vGPCR-like proteins.